An analysis of imperative sentences Of iron man 3 movie and their subtitling - Hardika, Septian Dwi, Dr. Dwi Haryanti, M.Hum, Dra. Malikatul Laila, M. Hum (2014)
The objectives of this study are to describe the types of imperative sentence in subtitling, and to describe the equivalence and non equivalence of imperative sentence with the target language in Iron Man 3 movie. The writer employs descriptive qualitative method. By this method, the writer uses the subtitling of Iron Man 3 movie as the source data, and the data are imperative sentence. The writer uses observation in collecting the data. The collected data are analyzed by comparison method. The results of this research paper show that first, the writer finds that there are 2 types of imperative sentence, namely; (1) positive imperative sentence consisting 165 data or 84. 62 %, (2) negative imperative sentence consisting 30 data or 15.38 %. The second, the writer finds that from 195 data, there are 175 data or 89.74 % belongs to equivalent subtitling and 20 data or 10.26 % belongs to non equivalent subtitling. So, the translation of subtitling Iron Man 3 is good.